The Ongoing Impact of Gender Pay Gap Transparency Legislation - Melanie K. Jones; Ezgi Kaya; Kerry L. Papps (Institute of Labor Economics (IZA), 2022)
This paper examines the ongoing impact of gender pay gap transparency legislation using a sudden COVID-19-induced temporary suspension to legislation in the UK. Compared to organisations that did not report during the suspension year, reporting organisations have a 6% lower gender pay gap a year later. This is driven by a relative increase in females in the top pay quartile at the same time as rising female concentration in the workforce overall. Further analysis supports the hypothesis that ongoing reporting is most effective in organisations with weaker pre-existing pressures to narrow their gender pay gap through female representation and voice.
Keywords: J31; J38; J78; 330; gender pay gap; pay transparency; equality legislation; COVID-19